2019
DOI: 10.1016/j.jaci.2018.06.046
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocyte–induced maturation protein 1 controls TH9 cell development, IL-9 production, and allergic inflammation

Abstract: Blimp-1 is a pivotal negative regulator of T9 differentiation and controls allergic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…Th2 cells express the transcriptional factors PU.1 and interferon regulatory factor (IRF) 4 in the presence of IL-4 and TGF- β , thus driving Th9 cell activation via the STAT6 signal [ 42 44 ]. Reversely, Th9 cells are suppressed by the overexpression of B lymphocyte-induced maturation protein 1 (Blimp-1) [ 45 ]. Th9 cells produce IL-9 to recruit and activate mast cells and B cells, associated with IgE elevation and corticosteroid resistance [ 46 , 47 ].…”
Section: Imbalance Of T Cells In Asthma Pathogenesismentioning
confidence: 99%
“…Th2 cells express the transcriptional factors PU.1 and interferon regulatory factor (IRF) 4 in the presence of IL-4 and TGF- β , thus driving Th9 cell activation via the STAT6 signal [ 42 44 ]. Reversely, Th9 cells are suppressed by the overexpression of B lymphocyte-induced maturation protein 1 (Blimp-1) [ 45 ]. Th9 cells produce IL-9 to recruit and activate mast cells and B cells, associated with IgE elevation and corticosteroid resistance [ 46 , 47 ].…”
Section: Imbalance Of T Cells In Asthma Pathogenesismentioning
confidence: 99%
“…Moreover, allergen-specific induction of IL-9 in PBMCs of atopic patients and in animal models has been reported [41]. H. contortus ESPs play crucial roles in parasite virulence as well as host-parasite interactions, mainly through the modulation of the host immune response [21,41]. In this study, the modulatory effects of ESPs on goat PBMCsderived Th9 cells production and immune response in vitro and during different stages of H. contortus infection in goat were evaluated.…”
Section: Discussionmentioning
confidence: 96%
“…Th9 cells in human diseases were known to contribute in both protective immune responses and pathological responses leading to immunemediated pathology [7]. Moreover, allergen-specific induction of IL-9 in PBMCs of atopic patients and in animal models has been reported [41]. H. contortus ESPs play crucial roles in parasite virulence as well as host-parasite interactions, mainly through the modulation of the host immune response [21,41].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most recent evidence has shown that Blimp-1 can repress the Th9 differentiation program and IL-9 production. Moreover, the inhibition of Blimp-1 by other cytokines related to Th9 cell differentiation is essential for high IL-9 production of Th9 cells (Benevides et al , 2019), which indicates that there are some negative regulators of Th9 programming, even though the exact mechanism remains to be elucidated.…”
Section: Transcription Factors Related To the Differentiation Of Th9 mentioning
confidence: 99%